MXene-Based Elastomer Mimetic Stretchable Sensors: Design, Properties, and Applications - Das, Poushali; Marvi, Parham Khoshbakht; Ganguly, Sayan; Tang, Xiaowu (Shirley); Wang, Bo; Srinivasan, Seshasai; Rajabzadeh, Amin Reza; Rosenkranz, Andreas (Nano-Micro Letters, 2024)
Flexible sensors based on MXene-polymer composites are highly prospective for next-generation wearable electronics used in human–machine interfaces. One of the motivating factors behind the progress of flexible sensors is the steady arrival of new conductive materials. MXenes, a new family of 2D nanomaterials, have been drawing attention since the last decade due to their high electronic conductivity, processability, mechanical robustness and chemical tunability. In this review, we encompass the fabrication of MXene-based polymeric nanocomposites, their structure–property relationship, and applications in the flexible sensor domain. Moreover, our discussion is not only limited to sensor design, their mechanism, and various modes of sensing platform, but also their future perspective and market throughout the world. With our article, we intend to fortify the bond between flexible matrices and MXenes thus promoting the swift advancement of flexible MXene-sensors for wearable technologies. Highlights: 1 MXenes, a new family of 2D nanomaterials, have been drawing notable attention due to their high electrical conductivity, processability, mechanical robustness and chemical tunability. 2 Flexible sensors based on MXene-polymer composites are highly prospective for next-generation wearable electronics used in human–machine interfaces. 3 With our article, we intend to fortify the bond between flexible matrices and MXenes thus promoting the swift advancement of flexible MXene-sensors for wearable technologies.